Answers

2015-03-15T13:47:37+05:30
Using midpoint formula , 
[ ( x1+x2 ) /2 , ( y1 +y2 ) /2 ]
substitute the values , 
(2,-3 ) =  [ (-1 + 5 )/2 ,( y+7 ) /2 ]
    now on comparing both LHS and RHS 
   -3 = ( y + 7 ) /2
  -3 × 2 = y + 7 
   -6 = y + 7 
   y = - 6 - 7
 ⇒ y  = -13 
therefore , 
A = ( -1 , -13 ) 



0
2015-03-15T14:00:31+05:30
Using midpoint formula , 
[ ( x1+x2 ) /2 , ( y1 +y2 ) /2 ] 
substitute the values , 
(2,-3 ) =  [ (-1 + 5 )/2 ,( y+7 ) /2 ]
    now on comparing both LHS and RHS 
   -3 = ( y + 7 ) /2
  -3 × 2 = y + 7 
   -6 = y + 7 
   y = - 6 - 7
 ⇒ y  = -13 
therefore , 
A = ( -1 , -13 ) 
0